Peningkatan Minat Penggunaan Kartu Kredit Syariah Melalui Pendekatan Kepercayaan, Sikap, dan Pendapatan - Russetyowati, Aprillia (Journal of Finance and Islamic Banking, 2018)
Sharia credits card has become a lifestyle of modern economy society in non-cash transactions. The use of sharia credit cards always raising period to period with various factors. These factors include trust, attitude, and income. The purpose of this study wants to determine the effects of trust, attitude, and income on interested in using sharia credit card. The study uses primary data from interviews with 38 lecturers of FEBI IAIN Surakarta which selected by boring sampling technique. The data had been analyzed by multiple linear regression. The result shows that each is of trust, attitude, and income affect positively and significantly to interested in using sharia credit card. The research gives a contribution to (a) academician; as an evidence of theory, (b) Sharia Bank; information to analyze the factors that affect to interested in using sharia credits.